Integrating Tahfidz Program Management for Comprehensive Student Character Development - Setiawan, Heru; Kausar, Shakila; Hakim, Muhammad Nur; Asmaul Husna, Fika (Kharisma: Jurnal Administrasi dan Manajemen Pendidikan, 2025)
Effective student management is vital for character development in educational settings. At MTs Tahfidz Al-Izzah Mojokerto, the Tahfidz program (Memorizing the Quran) significantly shapes students' academic achievements and moral foundations. This study analyses the planning and implementation of student management through the Tahfidz program. This research examines how student management, supported by the Tahfidz program, is planned and executed at MTs Tahfidz Al-Izzah Mojokerto and impacts students' character development. This research employed a qualitative descriptive approach with a case study method. Research data were collected through observations, interviews, and documentation from key stakeholders, including students, teachers, and administrators at the school. The study reveals that student management planning at MTs Tahfidz Al-Izzah starts with precise goal setting aligned with the school's vision and mission. The Tahfidz program is a central component structured with specific activity schedules. Implementation includes student selection via written tests and BTQ, followed by groupings for Tahfidz activities and continuous mentoring. The program effectively fosters students' academic success and strong moral character.  The research suggests that the Tahfidz program could be an effective model for student management in Islamic schools. Future research should explore the long-term impact of this program, identify factors that contribute to its success, and compare it with other character development programs to provide a broader perspective.